Effects of Strength Training on Muscle Properties, Physical Function, and Physical Activity among Frail Older People: A Pilot Study - Atle Hole Saeterbakken; Hilde Bremseth Bårdstu; Anine Brudeseth; Vidar Andersen (Journal of Aging Research)
The aim of this study was to determine the effects of a 10-week strength training intervention on isometric strength, rate of force development (RFD), physical function (stair climbing, rising from a chair, and preferred and maximal walking speed), and physical activity among frail elderly people receiving home-care services. Thirty participants were randomly assigned (by sex) to a control group (CON) or a strength training group (ST) performing a supervised training programme using elastic bands, box-lifting, and body weight exercises twice per week. Twenty-three participants were selected to complete the study (age 84.9 ± 6.1 years). For the ST, only improvement in muscle properties was the peak RFD in leg extension (p=0.04). No significant differences were observed in muscle properties for the control group (CON) (p=0.16–1.00) or between groups (p=0.39–1.00). There were no changes within and between the groups in physical function (p=0.12–0.19) or physical activity levels (p=0.06–0.73). The results of this pilot study did not demonstrate greater improvements in muscle properties and physical function and improved physical activity after attending a home-based resistance program compared to physical activity advise; however, larger population studies should examine these findings. This trial is registered with ISRCTN10967873.